Superpower Struggles : Mighty America, Faltering Europe, Rising Asia - Redwood, John (New York Palgrave Macmillan, 2005)
Since the war in Iraq of 2003, relations between the US and the EU have been strained and the UK has been increasingly regarded as the US Government's only dependable ally. In this new book John Redwood examines the growing conflicts between an EU flexing its muscles against the USA, and the dominance of the US global economy and military machine. He points to the phenomenal rise of China to say that whilst eyes.
Include Bibliography and Index
Keywords: World politics -- International economic relations